Distribution of Borrelia burgdorferi s.l. and Borrelia miyamotoi in Ixodes tick populations in Northern Germany, co‐infections with Rickettsiales and assessment of potential influencing factors. Issue 4 (27th June 2021) - Knoll, S.; Springer, A.; Hauck, D.; Schunack, B.; Pachnicke, S.; Fingerle, V.; Strube, C.
Abstract: To determine Borrelia spp. (Spirochaetales: Spirochaetaceae) prevalence and species distribution in Northern Germany, Ixodes ticks were sampled from April to October in 2018 and 2019 by the flagging method at three locations each in five regions. Analysis by quantitative real‐time PCR of 3150 individual ticks revealed an overall prevalence of 30.6%, without significant differences between tick stages (31.7% positive adults, 28.6% positive nymphs). Significant differences were observed in seasonal infection rates, but not between regions, landscape types or sampling years. Analysis of co‐infections with Rickettsiales indicated a negative association between Borrelia and Anaplasma phagocytophilum infection. The most frequent Borrelia species differentiated by Reverse Line Blot were B. afzelii and B. garinii / B. bavariensis, followed by B. valaisiana, B. burgdorferi sensu stricto, B. spielmanii and B. lusitaniae . Furthermore, B. miyamotoi was identified in 12.9% of differentiable samples. No effect of region nor landscape type on species composition was found, but significant variations in the distribution at the different sampling sites within a region were observed. The detected monthly fluctuations in prevalence and the differences in intra‐regional Borrelia species distribution underline the importance of long‐term and multi‐location monitoring of Borrelia spp. in ticks as an essential part of public health assessment. Abstract : Three thousand one hundred and fifty individual Ixodes ricinus ticks from Northern Germany were screened for Borrelia burgdorferi sensu lato and Borrelia miyamotoi, revealing an overall Borrelia prevalence of 30.6%. Analysis of co‐infections with Rickettsiales indicated a negative association between Borrelia and Anaplasma phagocytophilum infection. Monthly fluctuations in prevalence and intra‐regional variation in Borrelia species distribution underline the importance of long‐term and multi‐location monitoring as an essential part of public health assessment.